Strengthening Tawhid Education for Students at the Indonesian Da'wah Academy in Central Java - Aqidatul Izza; Muthoifin Muthoifin (Prosiding University Research Colloquium, 2022)
The purpose of this study is to implement the concept of strengthening monotheism education for female students at the Indonesian Da'wah Academy in Central Java, and to describe the results and impacts of implementing the concept of strengthening monotheism education for these female students. Data collection techniques from this research are observation, literature and documentation. The results show that the ideal Islamic education is very concerned with the implementation of monotheism education, because monotheism is the spirit of Islamic education, which consists of three main points: First, the monotheism rububiyyah contained in it, such as human nature as the basis of monotheism education, and the verses of Kauniah. as a means of monotheism education. Second, monotheism education uluhiyyah such as, the role of educators in monotheism education, evaluation in monotheism education and lifelong education. Third, the education of monotheism of asthma' wa al-nature. For the concept of strengthening monotheism education for students at the Indonesian Da'wah Academy in Central Java, it is very effective for teenagers who are at the stage of development who need guidance in strengthening monotheism so that they are able to live life with solid faith in Allah SWT, so a friendly method is needed so that students can easily in understanding monotheism correctly. The methods used are (1) hiwar method (2) story method (3) proverbs method (4) exemplary method (5) habituation method (6) 'ibrah and mau'idah methods (7) targhib and tarhib methods.